A hero of France : a novel - Furst, Alan (Random House, 2016)
"From the bestselling master espionage writer, hailed by Vince Flynn as "the best in the business," comes a riveting novel about the French Resistance in Nazi-occupied Paris. Paris, 1941. The City of Light, occupied by the Nazis, is dark and silent at night. Streetlamps are painted blue and apartment windows draped or shuttered in the blackout ordered by the Germans. But when the clouds part, the silvery moonlight defies authority, and so does a leader of the French Resistance, known as Mathieu. In Paris and in the farmhouses, barns, and churches of the French countryside, small groups of ordinary men and women are determined to take down the occupying forces of Adolf Hitler. Mathieu leads one such Resistance cell, helping downed British airmen escape back to England. This suspenseful, fast-paced thriller by the author whom Vince Flynn calls "the most talented espionage novelist of our generation" captures this dangerous time as no one ever has before. Alan Furst brings Paris and occupied France to life, along with courageous citizens who outmaneuver collaborators, informers, blackmailers, and spies, risking everything to fulfill perilous clandestine missions. Aiding Mathieu as part of his covert network are Lisette, a seventeen-year-old student and courier; Max de Lyon, an arms dealer turned nightclub owner; Chantal, a woman of class and confidence; Daniel, a Jewish teacher fueled by revenge; Joëlle, who falls in love with Mathieu; and Annemarie, a willful aristocrat with deep roots in France, and a desire to act. As the German military police heighten surveillance, Mathieu and his team face a new threat, dispatched by the Reich to destroy them all. Shot through with the author's trademark fine writing, breathtaking suspense, and intense scenes of seduction and passion, Alan Furst's A Hero of France is at once one of the finest novels written about the French Resistance and the most gripping novel yet by the living master of the spy thriller. Praise for Alan Furst "Furst never stops astounding me."--Tom Hanks "Suspenseful and sophisticated. No espionage author, it seems, is better at summoning the shifting moods and emotional atmosphere of Europe before the start of World War II than Alan Furst."--The Wall Street Journal "Though set in a specific place and time, Furst's books are like Chopin's nocturnes: timeless, transcendent, universal. One does not so much read them as fall under their spell."--Los Angeles Times "[Furst] remains at the top of his game."--The New York Times "A grandmaster of the historical espionage genre."--The Boston Globe"--